Multi-factor asset-pricing models under Markov regime switches: Evidence from the Chinese stock market - Jieting Chen; Yuichiro Kawaguchi (International Journal of Financial Studies, 2018)
This paper proposes a Markov regime-switching asset-pricing model and investigates the asymmetric risk-return relationship under different regimes for the Chinese stock market. It was found that the Chinese stock market has two significant regimes: a persistent bear market and a bull market. In regime 1, the risk premiums on common risk factors were relatively higher and consistent with the hypothesis that investors require more compensation for taking the same amount of risks in a bear regime when there is a higher risk-aversion level. Moreover, return dispersions among the Fama-French 25 portfolios were captured by the beta patterns from our proposed Markov regime-switching Fama-French three-factor model, implying that a positive risk-return relationship holds in regime 1. On the contrary, in regime 2, when lower risk premiums could be observed, portfolios with a big size or low book-to-market ratio undertook higher risk loadings, implying that the stocks that used to be known as 'good' stocks were much riskier in a bull market. Thus, a risk-return relationship followed other patterns in this period.
Keywords: G10; G12; C32; G15; 330; Markov regime-switching; anomaly; Chinese stock market; risk-return relationship